Case report: Benign and malignant tumors in adult patients with neurofibromatosis type 1: a comprehensive case series from a large oncologic reference center - Vidal-Millan, Silvia; Zatarain-Barrón, Zyanya Lucia; Daza-Galicia, Kena; Shveid Gerson, Daniela; Pichardo-Rojas, Pavel Salvador; Salazar-Pigeon, Alejandro; Wegman-Ostrosky, Talia (Frontiers in Oncology, 2024)
Neurofibromatosis type 1 (NF1) is a complex, multisystem disorder which is characterized, among other features, by a higher risk of developing benign and malignant tumors. Despite NF1 being one of the most common autosomal dominant genetic disorders, data from adult individuals in several world regions, remains elusive, including Hispanics.The present is a retrospective cohort study conducted among adult patients with a confirmed diagnosis of NF1 who attended a single cancer-reference center, the Instituto Nacional de Cancerología (INCan) in Mexico City from 2001 to 2021. Data was extracted from electronic health records and collected in an anonymous database by an NF1-expert physician in order to obtain demographic characteristics and detailed information regarding the development of tumors amongst this patient subgroup. All patients with malignant tumors or with benign tumors which severely affected their quality of life were included in this study.Patient records were reviewed from 2001 until 2021. A total of N=29 patients met the criteria, with a higher proportion of female compared with male subjects (N=22 [75.9%] vs. N=7 [24.1%]). Patients had a mean age at diagnosis of malignant tumors of 32.2 years (standard deviation 11.2 years). In terms of malignant neoplasms, the most frequent malignant tumor presented by patients in this cohort was malignant peripheral nerve sheath tumors (N=7; 24.1%), this was followed by breast cancer (n=4; 13.8% among all patients, 18.2% among female patients).Other tumors also identified in this cohort included melanoma, gastrointestinal stromal tumors, and rectal cancer.In Mexico patients diagnosed with NF1 develop diverse tumors as adults. As described in other studies the most frequent malignant tumor in this patient 3 population is the malignant peripheral nerve sheath tumor. Further studies are required to increase the scarce information available for adult Hispanics with NF1.